Micro finance – an anti poverty vaccine for rural india - K, Nithya Kala; K, Vidya Kala; S, Poornima (Journal of Management and Science, 2011)
Micro- finance interventions are well-recognized world over as an effective tool for poverty alleviation and improving soc ioeconomic status ofrural poor.In India too, micro- finance is making headway in its effort for reducing poverty and empowering rural women. The need of micro finance arises because the rural India requires sources of finance for poverty alleviation, procurement of agricultural and farms Micro finance is a programme to support the poor rural people to pay its debt and maintain social and economic status in the villages. As we know that India is agriculturebased economy, micro finance may be a tool to empower the farmers and ruralpeoples to make agriculture profitable. This research paper is highlighting a picture rural India as a developing segment for micro finance institutions.